The Development of Child Care Teacher’s Self-efficacy in Pediatric First-aid and Basic Life Support Skills in Child Development Center - Kummee , Sasithorn; Jaikla, Wanwika; Rengrew, Piyathorn; Mata , Chatsuda; Klintavorn, Wilaiwan (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental research was conducted through a two-group pretest-posttest design aimed to investigate the effect of self-efficacy enhancement program on knowledge, perceived self-efficacy and pediatric first-aid & basic life support (FA & BLS) skills among child care teachers. A total of 34 child care teachers were selected through purposive sampling based on inclusion criteria, divided into control and experimental groups of 17 participants each. The research instruments consisted of questionnaires on knowledge, perceived self-efficacy and the skill observation checklist for pediatric FA & BLS. The content validity index of the instruments were 0.8-1.0. The results revealed that: 1)The experimental group, after receiving the self-efficacy enhancement program, had the statistically significant higher mean score in knowledge, perceived self-efficacy, and pediatric FA & BLS skills compared to the control group. (p<.001) 2) After attending the program, the experimental group had the statistically significant higher mean score in knowledge, perceived self-efficacy, and pediatric FA & BLS skills compared to before attending the program. (p<.001) Therefore, the self-efficacy enhancement program should be implemented to promote knowledge, perceived self-efficacy and FA & BLS skills in child care teachers.